Gender representation in animal-related proverbs: Algerian vs. Jordanian Arabic - Madani, Zoubida; Abusalim, Nimer; Rayyan, Mohammad (Frontiers in Sociology, 2023)
The current study investigates the connotative meanings depicted in animal-related proverbs used to address and to describe women and men’s behavior in the Algerian and Jordanian societies; that is, how males and females are represented in the Algerian and Jordanian animal-related proverbs. To this end, a questionnaire containing 46 Algerian-animal related proverbs and 45 Jordanian ones was distributed to 30 native speakers of Algerian and Jordanian Arabic enrolled in the University of Jordan. Following Khan, Sardar, and Yousaf’s (2017) categories of analysis through a gender perspective which include inferiority, weakness, stupidity, ill-nature, sex object, ugliness, positive, and shrewd, the data analysis reveals that both Algerian and Jordanian animal-related proverbs have a variety of connotative meanings. The derogatory connotations that characterize women in both languages predominate among these meanings. The latter include characteristics such as weakness, stupidity, inferiority, cunningness, and trickery. Although the same characteristics are prevalent in data describing men in both languages, the image of women in Arab cultures is subordinate and has a denigrating profile. Furthermore, men continue to represent authority, control, superiority, and strength over women. Concerning the positive meanings, the data reveals the use of gazelle, peacock, partridge, cat and horse in depicting the beauty of women. Similarly, men’s positive characteristics such as strength, courage, and superiority are depicted via the utilization of horse, camel and lion.